2019
DOI: 10.1016/j.addbeh.2018.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous alcohol and marijuana use among underage young adults in the United States

Abstract: SAM use among young adults aged 19/20 in the US is relatively common, but especially so for those who began such use by age 18, highlighting the early onset and stability of this behavior. Among underage drinkers, SAM risk varies by sex, race/ethnicity, college status, and living arrangements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 29 publications
(48 reference statements)
7
81
1
Order By: Relevance
“…Marijuana use is also common among young adults, with 38% using in the past year (Schulenberg et al, ), and prevalence potentially increasing (e.g., White et al, ), especially in states like Washington where recreational marijuana is legal for adults (21+). Most young adults who use marijuana also use alcohol (Patrick et al, ), and recent research indicates simultaneous use of alcohol and marijuana is associated with greater alcohol use compared to drinking occasions without using marijuana among veterans (Metrik et al, ). SAM users have been found to be higher on risk factors such as perceived norms of peer SAM use and sensation seeking (e.g., Linden‐Carmichael et al, ; White et al, ).…”
Section: Sam Use and Consequences Among Young Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Marijuana use is also common among young adults, with 38% using in the past year (Schulenberg et al, ), and prevalence potentially increasing (e.g., White et al, ), especially in states like Washington where recreational marijuana is legal for adults (21+). Most young adults who use marijuana also use alcohol (Patrick et al, ), and recent research indicates simultaneous use of alcohol and marijuana is associated with greater alcohol use compared to drinking occasions without using marijuana among veterans (Metrik et al, ). SAM users have been found to be higher on risk factors such as perceived norms of peer SAM use and sensation seeking (e.g., Linden‐Carmichael et al, ; White et al, ).…”
Section: Sam Use and Consequences Among Young Adultsmentioning
confidence: 99%
“…Some young adults report engaging in SAM use in order to get “cross‐faded,” whereby young adults increase their levels of intoxication via SAM use (Patrick and Lee, ). Simultaneous use of both alcohol and marijuana use is prevalent among adolescents and young adults (Briere et al, ; Patrick et al, , ; Subbaraman and Kerr, ). Findings suggest that between 15 and 23% of adolescents and young adults engaged in SAM use within the past year (Subbaraman and Kerr, ; Terry‐McElrath et al, ).…”
Section: Sam Use and Consequences Among Young Adultsmentioning
confidence: 99%
“…It is critical to distinguish demographic correlates of SAM use from demographic correlates of alcohol and marijuana use. For example, gender differences in SAM use have been found among college students (Arterberry et al., ) as well as twelfth graders (Collins et al., ; Patrick et al., ), young adults (Patrick et al., ), and adults (Midanik et al., ), indicating that males, compared with females, are more likely to report SAM use. However, studies controlling for frequency of alcohol and marijuana use have found that women report more frequent SAM use (Collins et al., ; Hoffman et al., ; Terry‐McElrath et al., ).…”
Section: Normative Influences On Substance Usementioning
confidence: 99%
“…Inconsistent racial/ethnic group differences in SAM have also been observed. Some studies have found that white, compared with black, youth reports higher SAM use (Patrick et al., ; Terry‐McElrath et al., ), whereas others have found the converse (Arterberry et al., ; Collins et al., ) or no racial/ethnic group differences (Patrick et al., ). The current study fills a gap in the literature by controlling for existing differences in alcohol and marijuana use while examining sociodemographic differences in SAM use among college students.…”
Section: Normative Influences On Substance Usementioning
confidence: 99%
“…The most important individual factors reported are age and gender, with male and young adults exhibiting higher rates of alcohol use ( Canadian Centre on Substance Use and Addiction, 2017 ), impaired driving ( Butters et al, 2012 ; Canadian Centre on Substance Use and Addiction, 2018 ; Perreault, 2016 ), and involvement in motor vehicle collisions following cannabis use ( Asbridge et al, 2012 ; Robertson et al, 2017 ). Socioeconomic determinants such as education, employment, income and housing are also associated to drinking and driving: drinking drivers are more likely to have full-time employment and significantly higher average annual income ( Beirness & Davis, 2007 ), whereas full-time college attenders not living with parents are at greater odds of simultaneous alcohol and marijuana use ( Patrick, Terry-McElrath, Lee, & Schulenberg, 2019 ). Sociocultural factors, which include race and ethnicity, are also predictors of substance use, as cultural norms and practices influence behaviors in social settings ( Sudhinaraset, Wigglesworth, & Takeuchi, 2016 ).…”
Section: Introductionmentioning
confidence: 99%